Four-compartment muscle fatigue model to predict metabolic inhibition and long-lasting nonmetabolic components - Michaud, Florian; Beron, Santiago; Lugrís, Urbano; Cuadrado, Javier (Frontiers in Physiology, 2024)
Computational muscle force models aim to mathematically represent the mechanics of movement and the factors influencing force generation. These tools allow the prediction of the nonlinear and task-related muscle behavior, aiding biomechanics, sports science, and rehabilitation. Despite often overlooking muscle fatigue in low-force scenarios, these simulations are crucial for highintensity activities where fatigue and force loss play a significant role. Applications include functional electrical stimulation, motor control, and ergonomic considerations in diverse contexts, encompassing rehabilitation and the prevention of injuries in sports and workplaces. In this work, the authors enhance the pre-existing 3CCr muscle fatigue model by introducing an additional component of force decay associated with central fatigue and a long-term fatigue state. The innovative four-compartment model distinguishes between the short-term fatigued state (related to metabolic inhibition) and the long-term fatigued state (emulating central fatigue and potential microtraumas). Its validation process involved experimental measurements during both short-and long-duration exercises, shedding light on the limitations of the traditional 3CCr in addressing dynamic force profiles.